Calcinosis Universalis of the Elbow: A Rare Case with Classical Presentation - Sebastian Philipp Boelch; Thomas Barthel; Sascha Goebel; Maximilian Rudert; Piet Plumhoff (Case Reports in Orthopedics)
Juvenile Dermatomyositis (JDM) is a rare autoimmune disease in children and adolescents. In these patients calcinosis might be the most characteristic symptom. However there are only few reported cases of intramuscular calcinosis in Dermatomyositis. We report a case of calcinosis universalis (CU) of the elbow in JDM successfully treated with broaching. The patient, a 24-year-old woman, suffered from a long history of JDM. On examination she presented with a fistula lateral to the olecranon and pain of the right elbow joint. Plain X-rays displayed a diffuse pattern of multiple periarticular, subcutaneous, and intramuscular calcifications. The patient underwent surgery for histological and microbiological sampling as well as broaching. Intraoperatively sinus formation and subfascial hard calcium deposition were found. Due to the risk of collateral tissue damage, incomplete broaching was performed. A local infection with Staphylococcus was diagnosed and treated with antibiotics. On six-week and 30-month follow-up the patient was free of pain and had very good function. Calcifications on standard radiographs had almost resolved entirely. This case report gives a summary on calcinosis in Dermatomyositis and adds a new case of recalcitrant CU to the literature. Broaching surgery proved to be a reliable treatment option in symptomatic calcinosis.